Analysis of the Effect of Employee Welfare Levels and Punishments on Employee Performance with Work Discipline as Intervening Variables in Staff of RM. Djoelham Binjai Hospital - FA. Purba, Rosmery; Isa Indrawan, Muhammad (CV. Lafadz Jaya, 2023)
This study aims to analyze the effect of the level of employee welfare and punishment on employee performance with work discipline as an intervening variable. The location of the research was carried out at Rm Djoelham Binjai Hospital. The population in this study was 630 employees. Sampling using the Slovin formula was 245 employees for this study to collect respondent data by distributing questionnaires and surveys. The research model used was path analysis and measuring instruments from the study. This uses Sam PLS 3.3.3. The result of this study is that Work Discipline has no significant positive effect on Employee Performance. Punishment has a positive and significant effect on work discipline. Punishment has a positive and significant effect on employee performance. The level of Welfare has a positive and significant effect on Work Discipline. The level of Welfare has a positive and significant effect on Employee Performance. Punishment has a positive and insignificant effect on Employee Performance. Welfare Level influences Employee Performance through Work Discipline.